Efficacy and Safety of Risankizumab in Patients with Psoriasis Showing Suboptimal Response to Secukinumab or Ixekizumab: Results from a Phase 3b, Open-Label, Single-Arm (aIMM) Study - Richard B. Warren; Lev Pavlovsky; Antonio Costanzo; Michael Bukhalo; Neil J. Korman; Yu-Huei Huang; Georgios Kokolakis; Andreas Pinter; Nadia Ibrahim; Yanbing Zheng; Leonidas Drogaris; Vassilis Stakias; et al. (Adis, Springer Healthcare, 2024)
Abstract Introduction Risankizumab has demonstrated superior efficacy compared to other psoriasis treatments, including secukinumab, adalimumab, and ustekinumab; switching to risankizumab from other psoriasis treatments has shown superior clinical and quality of life (QoL) outcomes. We evaluated the efficacy and safety of directly switching patients with moderate-to-severe plaque psoriasis and a suboptimal response to interleukin (IL)-17 inhibitors (secukinumab or ixekizumab) to risankizumab. Methods This 52-week, phase 3b study enrolled patients (≥ 18 years) with moderate-to-severe plaque psoriasis who had previously been treated with the recommended dose of secukinumab or ixekizumab for ≥ 6 months but did not achieve an optimal response (static Physician's Global Assessment [sPGA] 2/3; body surface are [BSA] 3- < 10%). Patients received subcutaneous risankizumab (150 mg) without washout. The primary endpoint was the proportion of patients achieving sPGA of 0/1 at week 16. Secondary endpoints included sPGA 0/1 at week 52, sPGA 0, Dermatology Life Quality Index (DLQI) 0/1, and Psoriasis Symptoms Scale (PSS) 0 at weeks 16 and 52. Safety was monitored throughout the study. Results The study included 244 patients. sPGA 0/1 was achieved by 57.4% and 62.3% at week 16 and 52. At week 16, sPGA 0, DLQI 0/1, and PSS 0 were achieved by 20.5%, 40.2%, and 20.9%, respectively. At week 52, these proportions increased to 27.1% for sPGA 0, 47.2% for DLQI 0/1, and 27.5% for PSS 0. Most frequently reported adverse events (reported in ≥ 5% of patients) in risankizumab-treated patients were COVID-19 infection (8.6%) and nasopharyngitis (5.7%). No new safety signals were observed. Conclusions Directly switching to risankizumab improved outcomes and QoL in patients with moderate-to-severe psoriasis who had suboptimal responses to anti-IL-17 inhibitors (secukinumab or ixekizumab). The safety results are consistent with previously reported safety of risankizumab. This study supports the efficacy of risankizumab in patients previously treated with biologics, including IL-17 inhibitors, and suggests a direct switch to risankizumab for improved clinical outcomes and QoL. Clinical Trials ClinicalTrials.gov identifier: NCT04102007. Graphical Abstract